Democracy in Iran : why it failed and how it might succeed - Parsa, Misagh, 1945- (Harvard University Press, 2016)
Democracy in Iran examines democratization movements and processes in Iran over the last few decades, explains the causes of their failure, and suggests possible route to successful democratization. The book proposes a new framework for analyzing routes for democratization in the context of extremely authoritarian regimes in developing countries, specifically, the Islamic Republic of Iran. The new framework specifies the relevant variables in the economic, political, ideological, and social conditions of developing countries that determine alternative paths to democratization.--